2015
DOI: 10.4067/s0717-97072015000400008
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Status and Speciation in Chicken Heart Tissues

Abstract: SUMMARYThis study evaluated the total and main arsenic species in chicken heart tissues. The experimental study was carried out using two sets of samples. In the first one, 30-day-old chickens were exposed to sodium arsenate, using spiked drinking water. These chickens grew normally and were killed after fifty days of arsenic exposure. The second sets were edible chickens were nonexposed to sodium arsenate for a parallel study. The total arsenic and arsenic species content in the exposed samples were at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In general, MMA and DMA species have been considered important species in arsenic detoxification mechanisms, so it was surprising that DMA and MMA species were not detected in AU and the concentration of DMA was very low in the SAP and MAM (TABLE 7). Similar results were found in heart tissues of chickens (46). AsB is believed to have a very low toxicity and has been found in human serum (9); the presence of arsenobetaine was unexpected in this work; this organarsenical species enters human beings principally from marine foods and from agricultural products coming from In vivo methylation has long been proposed as an arsenic detoxification pathway for inorganic arsenic (22,47,48), but it has recently been shown that As(III)-MMA and As(III)-DMA, two intermediates in arsenate methylation, are more toxic to cells than As 3+ and A 5+ ions (22,47,49,50).…”
Section: +supporting
confidence: 74%
“…In general, MMA and DMA species have been considered important species in arsenic detoxification mechanisms, so it was surprising that DMA and MMA species were not detected in AU and the concentration of DMA was very low in the SAP and MAM (TABLE 7). Similar results were found in heart tissues of chickens (46). AsB is believed to have a very low toxicity and has been found in human serum (9); the presence of arsenobetaine was unexpected in this work; this organarsenical species enters human beings principally from marine foods and from agricultural products coming from In vivo methylation has long been proposed as an arsenic detoxification pathway for inorganic arsenic (22,47,48), but it has recently been shown that As(III)-MMA and As(III)-DMA, two intermediates in arsenate methylation, are more toxic to cells than As 3+ and A 5+ ions (22,47,49,50).…”
Section: +supporting
confidence: 74%
“…The samples were obtained from a population under study, made up of patients who have lived at least five years in the II Region of Chile. 32 Sample preparation were made on the bench of the "clean laboratory" inside a laminar flow hood (Labconco, Purifer Class II) using inert devices such as plastic and Titanium knives, agate grinding mortar, and scalpels, scissors and forceps of surgical stainless steel. After titanium clasp and fats residues removal, the tissues were rinsed with deionised water, separated as single samples and stored at -20 ºC.…”
Section: Experimental Samplesmentioning
confidence: 99%
“…After titanium clasp and fats residues removal, the tissues were rinsed with deionised water, separated as single samples and stored at -20 ºC. Specific patient's characteristics can be found in precedent work 32 and also in Table 1.…”
Section: Experimental Samplesmentioning
confidence: 99%
See 1 more Smart Citation